Pengembangan Modul Ajar PAI Berbasis Nilai Karakter Bangsa “Religius” pada Materi Menguatkan Iman di SMA PGRI 2 Jombang - Anggraini, Sofiah; Zulfah, Machnunah Ani; Fodhil, Muhammad (Lembaga Yasin AlSys, 2025)
This study is motivated by the low level of student understanding regarding religious character values in Islamic Religious Education (PAI), despite the implementation of the Kurikulum Merdeka. The objective of the research is to examine the planning and assess the effectiveness of a PAI teaching module integrated with national religious character values for Phase F at SMA PGRI 2 Jombang. The study employs a Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate). The define stage includes needs analysis, learner characteristics, and content analysis; the design stage involves formulating learning objectives, developing assessment instruments, and designing the module format; while the develop stage includes expert validation and field trials. Validation results show that the module is valid, with scores of 78% from practitioner experts, 89% from content experts, and 100% from module reviewers. Small- and large-scale trials demonstrate increased learning effectiveness, with an N-Gain score of 17.32%. The study concludes that the developed teaching module is effective in enhancing students’ understanding and religious attitudes and is suitable for use in character-based PAI instruction. The findings emphasize the importance of developing contextual teaching materials that integrate religious character values into the national curriculum to cultivate morally upright and nationally conscious generations. Keywords: Islamic Religious Education; Religious Character; Kurikulum Merdeka; Teaching Module; 4D Model